دور الاستراتيجيات البسيطة واستراتيجيات التذبذب لعقود الخيارات المالية في تحويط المحفظة الاستثمارية المثلى - HUSSAIN, IBRAHEEM MOHAMMED; QASIM, ADNAN SALEM (Journal of Duhok University, 2023)
The study aims to analyze the characteristics of investment in Common stocks in the Saudi financial market according to the single index model in order to determine each of the expected rate of return and the alpha and beta coefficient and to find both systemic and non-systematic risks and variance as a measure of the total risk and the coefficient of variation, and then build the optimal investment portfolio through the use of Quadratic programming for the balanced investor who characterized majority and rationality and who balances return and risk and desires to obtain the highest return within an acceptable risk level in order to reduce non-systematic risks. As for the systemic risks, which cannot be avoided by diversifying the components of the investment portfolio, they were hedged using simple strategies and volatility strategies for options contracts , After those contracts were priced according to the Black-Scholes model , the following strategies have been applied (long call option, long put option, long straddle, long strap, long strip) ; It was found through the results that the use of the quadratic programming method in allocating assets leads to improving the performance of the investment portfolio and reducing non-systematic risks, and that the use of an appropriate strategy for hedging with financial options contracts leads to achieving a greater return and less risks than the unhedged portfolio, that is, according to these strategies , systemic risks can be hedged, as it was shown from the performance indicators that the performance of the portfolios hedged with long call option and long strap strategy is better than the performance of the portfolio that is not hedged with these strategies and better than the performance of the market portfolio, while the performance of the portfolios hedged with long put option strategy, long straddle strategy and long strip strategy was bad because the average return for those portfolios was negative.